Tetrathienylethene‐based Positional Isomers with Aggregation‐induced Emission Enabling Super Red‐shifted Reversible Mechanochromism and Naked‐eye Sensing of Hydrazine Vapor. Issue 21 (2nd October 2019) - Song, Wenting; Zhi, Junge; Wang, Tianyang; Li, Bo; Ni, Shanshan; Ye, Yanchun; Wang, Jin‐Liang
Abstract: AIE‐active positional isomers, TTE‐ o ‐PhCHO, TTE‐ m ‐PhCHO and TTE‐ p ‐PhCHO, tetrathienylethene (TTE) derivates with peripherally attached ortho‐/meta‐/para ‐formyl phenyl groups, were designed and synthesized. The formyl substitution position can effectively modulate their photophysical properties, mechanochromism and fluorescent response to hydrazine. TTE‐ o ‐PhCHO and TTE‐ m ‐PhCHO exhibit remarkable AIE characteristics, and TTE‐ p ‐PhCHO possesses aggregation‐induced emission enhancement performance. They all exhibit high contrast mechanochromism, and TTE‐ m ‐PhCHO shows larger red‐shift (164 nm) than TTE‐ o ‐PhCHO (104 nm) and TTE‐ p ‐PhCHO (125 nm) due to the more twisted molecular conformation and much looser molecular packing. Moreover, TTE‐ o ‐PhCHO with a higher contrast color change can be used as ink‐free rewritable paper. In addition, TTE‐ p ‐PhCHO, as a turn‐on fluorescent probe, can selectively detect hydrazine with significant color changes that are visible by the naked eye . Therefore, the position dependence of groups would be an effective method to modulate the molecular arrangement, as well as develop AIE compounds for mechano‐stimuli responsive materials, ink‐free rewritable papers and chemosensors. Abstract : Three AIE‐active positional isomers based on tetrathienylethene attaching o ‐/ m ‐/ p ‐formylphenyl groups possess high contrast reversible mechanochromism and can be used in ink‐free rewritable papers. Furthermore, naked‐eye detection of hydrazine vapor was achieved.